Maria Stehle. Ghetto Voices in Contemporary German Culture: Textscapes, Filmscapes, Soundscapes. Rochester: Camden House, 2012. 205 pp. - Gizem Arslan (Studies in 20th & 21st Century Literature, 2015)
Review of Maria Stehle. Ghetto Voices in Contemporary German Culture: Textscapes, Filmscapes, Soundscapes. Rochester: Camden House, 2012. 205 pp.
Keywords: Germany; 20th and 21st century; inner cities; multiculturalism; contemporary cities; hip hop; minority literature; film and culture